Cultivation of Mesenchymal Bone Marrow Stem Cells on Glass-Crystalline Materials - Ladyhina, Valeriia I.; Kiroshka, Victoriia V.; Savvova, Ðžksana V.; Fesenko, Oleksiy I.; Bondarenko, Tatyana P. (Problems of Cryobiology and Cryomedicine, 2017)
Probl Cryobiol Cryomed 2017; 27(2):163.